Nutrition mapping in Tanzania: an exploratory analysis - Simler, Kenneth R. (International Food Policy Research Institute, 2006)
This paper explores the possibility of applying.. methods... known as small-area estimation to the study of children’s nutritional status as measured by anthropometry. This research in Tanzania is the first attempt to map nutrition in an African country using small-area estimation. The study asks two questions: first, is nutrition mapping feasible? Second, what is the spatial distribution of undernutrition in Tanzania?...The answer to the question of whether nutrition mapping is feasible is a qualified “yes.” Although the models of children’s nutritional status are not as successful as poverty mapping models at explaining variation, the spatial pattern of undernutrition at the district level seems plausible.